To determine the number of solutions for the equation \( ax + c_1 = bx + c_2 \), let's rearrange it:
-
Subtract \( bx \) from both sides: \[ ax - bx + c_1 = c_2 \] \[ (a - b)x + c_1 = c_2 \]
-
Now, isolate \( x \): \[ (a - b)x = c_2 - c_1 \] \[ x = \frac{c_2 - c_1}{a - b} \]
Now we can analyze the number of solutions based on the values of \( a \) and \( b \):
-
If \( a - b \neq 0 \):
- This means \( a \neq b \), and the equation will have one unique solution: \[ x = \frac{c_2 - c_1}{a - b} \]
-
If \( a - b = 0 \) (or \( a = b \)):
- The equation simplifies to \( c_1 = c_2 \):
- If \( c_1 = c_2 \), then the equation is true for all \( x \) (infinitely many solutions).
- If \( c_1 \neq c_2 \), then the equation is false for all \( x \) (no solutions).
- The equation simplifies to \( c_1 = c_2 \):
In summary:
- One solution: \( a \neq b \)
- Infinitely many solutions: \( a = b \) and \( c_1 = c_2 \)
- No solutions: \( a = b \) and \( c_1 \neq c_2 \)